2018
DOI: 10.1002/jat.3625
|View full text |Cite
|
Sign up to set email alerts
|

E‐cigarettes: voltage‐ and concentration‐dependent loss in human lung adenocarcinoma viability

Abstract: E-cigarettes are used by millions of people despite the fact that the harmful effect of aerosol emitted from these products to the human organism is still not clear. In this paper, toxicity of vapor generated using different solutions and battery output voltage on A549 cells viability is presented. The obtained EC values for commercially available propylene glycol/glycerol solution 1:1 e-liquids based on 3.2 V (0.127%), 4.0 V (0.112%) and 4.8 V (0.038%) were about 1.5-4.5 times higher than in tobacco smoke (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…We used a shorter puff duration, which occurred due to the safety feature of the device. As a result, the utilized puff duration is more comparable with cigarette use, although similar puff durations have been used by others (Anderson, Majeste, Hanus, & Wang, ; Leslie et al, ; Otręba et al, ). More recent topography data have revealed that puffing behaviour is highly heterogeneous with significant inter‐ and intra‐user variation.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…We used a shorter puff duration, which occurred due to the safety feature of the device. As a result, the utilized puff duration is more comparable with cigarette use, although similar puff durations have been used by others (Anderson, Majeste, Hanus, & Wang, ; Leslie et al, ; Otręba et al, ). More recent topography data have revealed that puffing behaviour is highly heterogeneous with significant inter‐ and intra‐user variation.…”
Section: Discussionmentioning
confidence: 70%
“…In line with our data, Bengalli et al reported no cytotoxic or inflammatory effect of EVE with and without nicotine, or with the addition of tobacco flavour on A549 cells (Bengalli et al, ), whereas others have seen some cytotoxic effects (Cervellati et al, ). As stated earlier, this could be due to differing E‐liquids, devices and device settings, as shown by Otręba and colleagues with increasing battery output voltage (Otręba, Kosmider, Knysak, Warncke, & Sobczak, ). A study comparing the toxicity of a range of EVEs with CSE using a variety of human cell lines, including BEAS‐2B, also showed that CSE proved more cytotoxic than EVEs, and that the decrease in cell viability after EVE exposure was dependent on brand, flavour and cell line used in the model (Leslie et al, ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, many of these flavoring agents are categorized as “generally recognized as safe” by the Flavor Extracts Manufacturers Association for ingestion; however, the classification does not pertain to inhalation. To this point, several in vitro studies using human, rat or mouse cells demonstrate that some flavoring agents in e‐liquids are cytotoxic (Bahl et al, ; Behar et al, ; Behar, Wang, & Talbot, ; Farsalinos et al, ; Lerner et al, ; Otreba, Kosmider, Knysak, Warncke, & Sobczak, ; Rowell et al, ). Cinnamon‐flavored e‐liquids are particularly cytotoxic in rat cardiomyoblasts and human CALU3 airways cells (Farsalinos et al, ; Rowell et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that the type of NVP device used can influence nicotine delivery and exposure to toxicants [6,7]. In a convenience sample of experienced US vapers surveyed in 2014, Yingst et al showed that most vapers began with a disposable or 'cigalike' device (59%) and nearly two-thirds transitioned to a refillable device, whereas only 6% of those who began on a refillable device made the reverse move [8].…”
Section: Introductionmentioning
confidence: 99%